The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1016/j.enganabound.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Shape design sensitivity analysis with respect to the positioning of features in composite structures using the boundary element method

Abstract: This paper presents the application of the boundary element method to the shape design sensitivity analysis of composite structures with holes and cutouts. A two-dimensional anisotropic domain which contains a number of voids of arbitrary shapes will be considered.The objective is to perform the design sensitivity analysis of the structure with respect to the translation and rotation of the voids using the boundary element method. A directly differentiated form of the boundary integral equation, with respect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The advantage of the proposed method was that it can be applied to any geometry, not necessarily regular shapes. However, when entire segments of the boundary or domain were governed by a single variable such as radius, the relevant velocity terms were applied together in the sensitivity analysis with respect to that variable [19] to determine the gradients of the objective function and the constraints. It was shown that, if the entire boundary is governed by a single geometric variable (), such as radius, the material derivative F with respect to the variable can be written as Here, using a similar approach the crack length of arbitrary geometric shape is selected as the shape design variable.…”
Section: Vmentioning
confidence: 99%
See 3 more Smart Citations
“…The advantage of the proposed method was that it can be applied to any geometry, not necessarily regular shapes. However, when entire segments of the boundary or domain were governed by a single variable such as radius, the relevant velocity terms were applied together in the sensitivity analysis with respect to that variable [19] to determine the gradients of the objective function and the constraints. It was shown that, if the entire boundary is governed by a single geometric variable (), such as radius, the material derivative F with respect to the variable can be written as Here, using a similar approach the crack length of arbitrary geometric shape is selected as the shape design variable.…”
Section: Vmentioning
confidence: 99%
“…The objective of the work in Ref. [19] is directed towards the optimal positioning of features in anisotropic structures for maximum stiffness, while the weight remains unchanged. For this purpose, the design sensitivity analysis, with respect to the translation and rotation of the voids of arbitrary shapes using the BEM, was performed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The boundary element method being a surfaceoriented technique is well suited for shape optimization problems [1][2][3][4][5]. Tafreshi, A. Feb. 2009 In : Engineering Analysis with Boundary Elements.…”
Section: Introductionmentioning
confidence: 99%